PIBID: apresentando a proposta do subprojeto de Educação Física Alegrete/RS - Nunes, Marluã Alende; Maia, Marjana; Cruz, Marcélle; Vieira, Matheus; Dias, Edgar; Schirmer, Tamires; Guterres, Rodrigo (Revista Didática Sistêmica, 2015)
Não Disponível.